A review on effects of human activities on aquatic organisms in the Yangtze River Basin since the 1950s. Issue 1 (28th August 2022) - Yin, Senlu; Yi, Yujun; Liu, Qi; Luo, Qiyong; Chen, Kebing
Abstract: The Yangtze River is the longest river in China, with abundant water resources, high water energy reserves, and rich biodiversity. Human activities have greatly changed the hydrology and ecology of the Yangtze River Basin since the 1950s. The aquatic biodiversity in the Yangtze River Basin has declined sharply, while the amount of fishery in the Yangtze River has been maintained due to higher intense of fishing, artificial proliferation intervention, and other factors. Human activities including overfishing, water polluting, damming, reclaiming wetlands, shipping and shoreline development, species introduction, and so forth have had great influence on aquatic ecosystems. This paper also reviewed the measures implemented to protect the aquatic ecosystems of the Yangtze River. By reviewing the evolutionary trend of aquatic organisms in the Yangtze River Basin and the related human activities, this paper helps to better understand the biodiversity of the Yangtze River, and requires more attention on the continuous impact of human activities, as well as the effectiveness of protection measures under the new situation of Yangtze River protection.